2008
DOI: 10.1001/archgenpsychiatry.2007.40
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Young Adults With Very Low Birth Weight

Abstract: This is the first study (to our knowledge) to show that intrauterine growth pattern may modify associations between VLBW and depression. Intrauterine growth retardation rather than VLBW per se may pose a risk of depression in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(41 citation statements)
references
References 37 publications
2
37
1
Order By: Relevance
“…In multivariable analysis, in Ribeirão Preto, the association between low birth weight and the presence of depressive symptoms remained significant even after adjusting for preterm birth, indicating that intrauterine growth restriction rather than preterm birth might explain this association. Similar results were found in a study in Helsinki [43], where intrauterine growth restriction (IUGR) was also identified as a risk factor for depression.…”
Section: Discussionsupporting
confidence: 88%
“…In multivariable analysis, in Ribeirão Preto, the association between low birth weight and the presence of depressive symptoms remained significant even after adjusting for preterm birth, indicating that intrauterine growth restriction rather than preterm birth might explain this association. Similar results were found in a study in Helsinki [43], where intrauterine growth restriction (IUGR) was also identified as a risk factor for depression.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies suggest that the increased risk for mental disorders associated with preterm birth may characterize especially those preterm individuals who were born small for gestational age [SGA; defined as birth size at 42 standard deviations (S.D.s) or below the 5th or 10th percentile of that predicted by their gestational age; Laursen et al 2007;Räikkönen et al 2008;Strang-Karlsson et al 2008;Monfils Gustafsson et al 2009]. In fact, previous studies have shown that at least until young adulthood, individuals born SGA are at increased risk of severe mental disorders independently of their gestational age (Abel et al 2010;Niederkrotenthaler et al 2012;Nosarti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They range from general learning problems [7], [17] to an increased risk for depression [18], schizophrenia [19], anxiety, attention and hyperactivity disorders [20]. Additionally, a reduced brain volume has been found in these children ([11], [21], see also [22]).…”
Section: Introductionmentioning
confidence: 99%